Tadarruju al Hājāti li Syakhṣaini Ra’īsaini fī al Filmi Barakatin Yuqābilu Barakatan (Dirāsatun Sikūlūjiatun Adabiatun li Abrāhām Maslow) - Khoirunnisya, Tri Nanda; Walidin, Muhammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
This study aims to determine the level of fulfillment of Abraham Maslow's hierarchy of needs on the characters Barakah Urabi and Bibi Harith, in the film Barakah Yuqabil Barakah (BYB) by Mahmoud Sabbagh. In achieving this the researcher conducted two analyses. Firstly, analyzing the form of characterizations in the film BYB to find out the classification of characters and the form of characterizations in the characters Barakah Urabi and Bibi Harith. Secondly, analyzing the personalities of the figures Barakah Urabi and Bibi Harith which includes how they fulfill the hierarchy of needs from the lowest to the highest. The theory used in this study is the Structural and humanistic theory of Abraham Maslow's personality, through qualitative methods. The analysis phase was carried out by collecting data relevant to the technique of reading, observing, taking notes, then analyzing it according to Abraham Maslow's humanistic personality theory, after which the data was presented descriptively with documentation. The results of the study show that there are two main characters in the film BYB who have different characters. Barakah Urabi is described as a simple man, while Bibi Harith is described as a modern woman. These two figures fulfill all their needs. These needs include: physiological needs, safety, love and belonging, self-esteem, and self-actualization.